Sebuah Pandangan Mengenai Mater! Pelajaran Geografi Di Pra-Perguruan Tinggi = An idea on Geography Subject at the Pre-University - Bintarto, R. (Majalah Geografi Indonesia, 1988)
Education of geography for SLTA students (secondary school) is aimed at teaching students to behave as members of a modern Indonesian society with self-confidence and capable of solving a variety of daily-life problems both at pesent and in the .future. Some problems which arise in the Indonesian society are both of a social and physical nature. For that reason, attention should be paid to these problems in the reaching and learning materials for the SLTA, especially during the geography lessons. Moreover, geography based on the study of social and physical phenomena on a national and international level, should widen the scope of perception of the students. Concerning the criteria for lesson materials, on the one hand the geography subject should comply with the SLTA. curriculum and on the other hand, the physical and human aspects of the subject should reflect daily life realities. The materials should be taught as a whole package, not as separated fragments of physical and human aspects, to satisfy the geographical paradigm. Another aspect which should be given due consideration, is the continuation of the geography education from nursery school up to the university, with the teaching materials adjusted to the respective school levels. A well-designed balance of geography education in the school curricula and lesson materials is thought to intensify logical deductive thinking and stimulates character development of the students. It is therefore the right moment for geography teachers to reconsider the geography education in the SLTA curriculum, to improve the teaching package whenever necessary and publish books on geography topics.